Correlation between 18F-FDG maximum standardized uptake value with CD147 expression in lung adenocarcinomas: a retrospective study - Fei Guo; Xueyan Li; Guodong Yao; Guangchun Zeng; Lijuan Yu (PeerJ, 2019)
Background The pro-tumoral action of the cluster of differentiation 147 (CD147), which is associated with the chemotherapy resistance of lung adenocarcinoma, is partly due to accelerated tumor cell glycolysis. 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) metabolic parameters included maximal standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), metabolic tumor volume (MTV), and total lesion glycolysis (TLG), which are non-invasive markers of the glucose metabolism of tumor cells in vivo. This study aimed to clarify the correlation between PET metabolic parameters and CD147 expression, and to evaluate the prognostic value of CD147 expression in resectable lung adenocarcinoma patients. Methods A total of 89 lung adenocarcinoma chemotherapy-naive patients who underwent 18F-fluorodeoxyglucose positron emission tomography and computerized tomography scan before pulmonary surgery were retrospectively analyzed. The PET metabolic parameters were calculated by 18F-FDG PET imaging, and CD147 expression was analyzed by immunohistochemistry. SUVmax, SUVmean, MTV, and TLG compared for their performance in predicting the expression of CD147 were illustrated with statistical analysis. All patients were then followed-up for survival analysis. Results The SUVmax was significantly correlated with the CD147 expression and was the primary predictor for the CD147 expression of lung adenocarcinoma. A cut-off value of the SUVmax, 9.77 allowed 85.1% sensitivity and 64.3% specificity for predicting the CD147 positive lung adenocarcinoma. CD147 expression was correlated with tumor differentiation and metastasis. Univariate survival analysis showed that CD147 expression was significantly associated with a shorter overall survival (OS) time. Multivariate analysis revealed that CD147 was an independent prognostic factor of lung adenocarcinoma patients. Conclusion The SUVmax of a primary tumor measured with 18F-FDG PET may be a simple and non-invasive marker for predicting CD147 expression in lung adenocarcinoma. CD147 is an independent prognostic factor related to OS of postoperative lung adenocarcinoma patients.